Influence of Magnetized Water and Nitrogen Bio-fertilizers on the Quantity and Quality Features of the Butternut Squash Cucurbita moschata - Ali, Abbas Fadhil; Alsaady, Majida Hadi Mahdi; Salim, Hussein Ali (Iraqi Journal of Science, 2019)
The present study was carried out at Baqubah Nursery, Directorate of Agriculture, Diyala Province, Iraq, during the period of March to October 2017, to investigate the effects of magnetized water with bio and chemical fertilizers on the butternut squash. A factorial experiment with three replications was conducted and two factors were investigated; the state of water (magnetized water and non-magnetized water) and the fertilizer type (chemical fertilizer: urea 100 kg N/ hectare; bio-fertilizers: Azotobacterchroococcum and Azospirillumbrasilense + chemical fertilizer in 1:1 ratio). The results revealed that the magnetized water with bio + chemical fertilizers recorded the highest rate of fruit weight that reached 786.0 ,807.3 and 775.3 g at the first, second and third harvests, respectively. The effect of the magnetized water was significant on the rate of fruit yield/plant which reached 3745.0 g at the first harvest, while bio + chemical fertilizer recorded the highest rate that reached 2419.8 and 1404.3 g at the second and the third harvests, respectively. Magnetized water with bio + chemical fertilizers showed significant increments in total yield / plant (7822.3 g) and total yield / hectare (31289.3 kg). The treatment with magnetized water and bio and chemical fertilizer were significant in fruit content of total soluble solid (TSS %) after 185 days, which reached 13.0 % and 12.2 %, respectively, while bio + chemical fertilizer was superior in the yield of fructose sugar and fibers which reached 10.4 and 12.7 % , respectively.